Development of Interactive Learning Media Based on Autoplay Media Studio on the Theory of Entry and Spread of Islam in Indonesia Class X SMAN 14 Bandar Lampung. - Fradila, Renata; Maskun, Maskun; Sumargono, Sumargono (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2023)
Learning media is an important tool used by educators to deliver messages or information to students. The development of increasingly sophisticated technology is a demand for educators to develop learning media. The development of interactive learning media based on autoplay studio media requires problems with limitations and the use of history learning media which seems monotonous at SMAN 14 Bandar Lampung, namely teachers only use media such as textbooks and powerpoint. The problem in this research is how to develop interactive learning media based on autoplay media studio on the theory of entry and spread of Islam in Indonesia for class X at SMAN 14 Bandar Lampung. The purpose of this research is to develop interactive learning media based on autoplay media studio on the theory of entry and spread of Islam in Indonesia for class X at SMAN 14 Bandar Lampung. This study uses the ADDIE development model which consists of several stages, namely analysis, design, development, implementation, evaluation. Data collection techniques used are observation, interviews, and questionnaires. The development research instruments used to collect research data were expert validation questionnaires and student response questionnaires. Based on the results of the study it can be concluded that interactive learning media based on autoplay media studio was developed in several stages. The results of the validation of the material experts obtained a percentage of 93.3% with a very valid category, the validation of media experts obtained a percentage of 91.4% with a very valid category, and the results of students' responses to the media during trials carried out an average percentage of > 85%. very positive category. Thus, this learning media is considered very valid so that it is very suitable to be used as a supporting media in the history learning process. Keywords: Development, Media, Interactive, Autoplay Media Studio, History.